Mechanisms for CpG Island Methylation during X chromosome inactivation - Yasmin, K (2024)
During early development in female mammals one of the two X chromosomes is transcriptionally silenced, ensuring an equal dosage of X-linked genes relative to their XY male counterparts. This phenomenon is termed X chromosome inactivation (XCI). XCI is initiated by expression of the long noncoding RNA (lncRNA) Xist from the inactive X chromosome (Xi). Xist orchestrates molecular pathways in cis to establish transcriptional silencing and heterochromatinization of the Xi in a multi- stage process. A late stage of XCI is the methylation of CpG-rich regions associated with gene promoters, called CpG Islands (CGIs). Mammals express two highly similar de novo DNA methyl transferases, DNMT3A and DNMT3B. Intriguingly, only DNMT3B is crucial for Xi CGI methylation, and it is unclear what factor(s) imparts this specificity.